Sex Differences in Psychiatric Comorbidity and Plasma Biomarkers for Cocaine Addiction in Abstinent Cocaine-Addicted Subjects in Outpatient Settings - Pedraz, María; Araos, Pedro; García-Marchena, Nuria; Serrano, Antonia; Romero-Sanchiz, Pablo; Suárez, Juan; Castilla-Ortega, Estela; Mayoral-Cleries, Fermín; Ruiz, Juan Jesús; Pastor, Antoni; Barrios, Vicente; Chowen, Julie A.; et al. (Frontiers in Psychiatry, 2015)
There are sex differences in the progression of drug addiction, relapse and response to therapies. Because biological factors participate in these differences, they should be considered when using biomarkers for addiction. In the current study, we evaluated the sex differences in psychiatric comorbidity and the concentrations of plasma mediators that have been reported to be affected by cocaine. Fifty-five abstinent cocaine-addicted subjects diagnosed with lifetime cocaine use disorders (40 men and 15 women) and 73 healthy controls (48 men and 25 women) were clinically assessed with the diagnostic interview ‘Psychiatric Research Interview for Substance and Mental Disorders’. Plasma concentrations of chemokines, cytokines, N-acyl-ethanolamines and 2-acyl-glycerols were analyzed according to history of cocaine addiction and sex. The results showed that the chemokine concentrations of CCL2/MCP-1 and CXCL12/SDF-1 were only affected by history of cocaine addiction. The plasma concentrations of IL-1β, IL-6, IL-10 and TNFα were higher in control women relative to men, but these concentrations were reduced in cocaine-addicted women. Cytokine concentrations were unaltered in addicted men. Regarding fatty acid derivatives, history of cocaine addiction had a main effect on the concentration of each acyl derivative; whereas N-acyl-ethanolamines were increased overall in the cocaine group, 2-acyl-glycerols were decreased. Interestingly, POEA was only increased in cocaine-addicted women. Regarding psychiatric comorbidity in the cocaine group, women had lower incidence rates of comorbid substance use disorders than did men. For example, alcohol use disorders were found in 80% of men and 40% of women. In contrast, the addicted women had increased prevalences of comorbid psychiatric disorders (mood, anxiety and psychosis disorders). These results demonstrate the existence of a sex influence on plasma biomarkers for cocaine addiction and on the presence of comorbid psychopathologies.